Взаємозв’язок між деякими параметрами фітогенного поля та морфометричними показниками пагонів деревних рослин - Gorelov, A.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
The significance of correlation coefficient between some phytogenic field parameters and morphometrical shoot indexes some woody plant species are analyzed. It is established that plant morphometrical parameters are mostly connected with biolocational potential and lightning, less – with temperature and air humidity.